AMBIENT MARKETING AS AN UNCONVENTIONAL FORM OF COMMUNICATION (Research Bulletins of the Faculty of Economic Sciences, 2018)
This article discusses issues related to enterprise - market communication systems. It presents the character, essence and tools of ambient marketing and describes the functioning of guerrilla marketing, viral marketing, buzz marketing, aromarketing and gender marketing. The purpose of this article is to determine the impact of ambient marketing on consumers' purchasing decisions and the effectiveness analysis of this form in the promotion of the material goods. The key research problem is connected to searching for answers to questions comparing ambient advertisements with the classic ones in terms of attracting the attention of the audience, the degree of memorisation, effectiveness and questions about the impressions that are generated by ambient actions. The research was based on an internet survey. As a result of the research it was found that more and more companies will use ambient marketing in practice because their existing marketing activity has fatigued the audience.
Keywords: communication, consumers, advertisement, society, modern mass media